Anatomical variations in the tibial insertion of the Anterior Cruciate Ligament: An MRI study - Henry Magill; Branavan Rudran; Clare Cullen; Neil Jain (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Anterior Cruciate Ligament (ACL) reconstructive surgery provides good to excellent (75% to 97%) outcomes overall in terms of joint stability, symptom improvement and return to pre-injury activity  [1]. Between 0.7 and 20% of patients, however, undergoing surgery will experience persistent instability symptoms due to ACL graft failure  [2]. Femoral and tibial tunnel malposition may cause flexion and extension deficits and ultimately lead to graft failure  [3].